Analisis Pendapatan Usaha Ternak Babi Di Desa Passo Kecamatan Baguala Kota Ambon - Hatalaibessy, Erna; Tomatala, George S. J.; Matatula, Michel J. (Universitas Pattimura, 2024)
This research aims to find out how much production costs and income farmers earn from pig farming. The research was carried out in Passo Village, Baguala District, Ambon City, using a survey method with case study method techniques and determining respondents using purposive sampling. The number of respondents was 44 breeders. Data collection was carried out through direct interviews, observation and documentation. Data analysis was carried out descriptively by calculating production costs, income and Revenue Cost Ratio (R/C). The research results show that the average production cost (explicit and implicit) is IDR 18,444,447.45/year. Average fixed costs Rp. 13,851,996.81/year (74.98%). Average variable costs Rp. 4,617,046.00 (25.02%). The average income of farmers is IDR 26,169,565.00/year. If the calculation is explicit, the income is IDR 21,033,103.00 and explicitly + implicitly IDR 7,725,117.55. The R/C Ratio (Explicit) value is 5.10 and the R/C Ratio (Explicit + Implicit) is 1.42. With an R/C Ratio value of ˃1, the pig farming business in Passo Village, Baguala District, is considered economically profitable and worth pursuing.